New and future developments in microbial biotechnology and bioengineering aspergillus system properties and applications - Gupta, Vijai Kumar (Elsevier, 2016)
New and Future Developments in Microbial Biotechnology and Bioengineering: Aspergillus System Properties and Applications provides information on emerging issues related to recent advancements in aspergillus research and its applications in bioprocess technology, chemical engineering, genome biology, molecular taxonomy, secondary and metabolite production, industrial process and biofuels/bioenergy research, and alternative fuel development. The book covers the various novel enzymes secreted by these fungi and their specific use in the food, textile, pulp and paper, biocellulosic ethanol production, and other industries. The book describes research and experimentation on aspergillus activity and directly connects them to their use in bioprocess technology, chemical engineering, bioremediation process, secondary metabolite production, pharmaceutical processes, protein production, industrial process, biofuels/bioenergy research, and alternative fuel development. Readers will find this book to be an indispensable resource for biotechnologists, biochemical engineers, biochemists, microbiologists, bioinformatics researchers, and other biologists who are interested in learning about the potential applications of these fungi.--Provided by publisher.